Changes in work behavior during pregnancy in rural Anhui, China from 2001–03 to 2009: a population based cross-sectional study. Issue 1 (December 2016) - Neupane, Subas; Nwaru, Bright; Wu, Zhuochun; Hemminki, Elina
Abstract Background In low- and middle-income countries, many women continue working later into pregnancy. In our recent study on some areas in rural China, most women stopped working already during the first trimester (≤3 months) of pregnancy. In this paper we aimed to explore whether stopping work during early pregnancy has changed over an 8 year period (between 2001–03 and 2009); we also studied whether the reasons for stopping work early were the same in the two time periods. Methods A population-based cross-sectional survey with a representative sample of new mothers was carried out in one rural county in Anhui Province in 2001–03 (N = 1479 respondents) and in two other rural counties in 2009 (N = 1574 respondents). Both surveys were used to evaluate prenatal care interventions not related to work behavior. The surveys targeted all women who had recently given birth. Multilevel logistic regression analysis was used to examine the determinants of work behavior in the two time periods. Results There was a big change in the working behavior between the two survey years: in the period 2001–03 6 % and in 2009, 53 % of pregnant women stopped working at ≤3 months (percentage change 839, 95 % CI −15.90 to 1694.49). In 2001–03, 30 % and in 2009, 23 % of pregnant women worked the same as before pregnancy (percentage change −22.30, 95 % CI −90.28 to 45.68). In both time periods women with two children were less likely to stop work at ≤3 months of pregnancy. Non-farmers were more likely in 2001–03 but less likely in 2009 to stop work at ≤3 months of pregnancy. Women with medium township-level income were more likely to maintain the same level of work as before pregnancy in 2001–03, while in 2009 women with high township-level income were less likely to work the same. Conclusion Stopping work very early during pregnancy appeared to have become very common from 2001–3 to 2009 in rural Anhui, China and was not explained by women's background characteristics.